SMART VILLAGE AS A FORM OF SUSTAINABLE VILLAGE DEVELOPMENT IN LAMPUNG PROVINCE - Fitriani, Yuyun (Universitas Negeri Medan, 2024)
The current smart village concept is an activity to optimize village government services by increasing the use of information technology to support the progress of village communities in Lampung Province . The purpose of writing this article is to provide an overview of smart village development as a form of sustainable development in Lampung Province. The method used in this research activity is a qualitative method with a descriptive approach. The research results show that the implementation of smart villages in Lampung Province has gone well. Based on the three main elements of a smart village, namely smart government, smart community, and smart environment shows that these three elements can influence each other and can be a determining factor in the quality of public services in the village